Fundamentals of power integrity for computer platforms and systems - DiBene, J. Ted., II (Joseph Ted) (John Wiley & Sons, 2014)
"Power integrity is the study of power distribution from the source to the load and the system level issues that can occur across it. For computer systems, these issues can range from inside the silicon to across the board and may egress into other parts of the platform, including thermal, EMI, and mechanical. With a focus on computer systems and silicon level power delivery, this book sheds light on the fundamentals of power integrity, utilizing the author's extensive background in the power integrity."--Provided by publisher.